A comparison of moss diversity in the lowland tundra and mountain tundra in the Kola Subarctica (Murmansk Region, Russia) (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
In total 390 species were found in lowland and mountain tundra habitats in Murmansk Region. 242 species were observed in both mountain tundra belt and zonal lowland tundra. Species diversity and composition of ecological and georgaphic groups of mosses was compared between lowland vs. mountain tundra.
Keywords: bryophytes, tundra zone, mountain tundra belt, moss flora, ecology of mosses.